2013
DOI: 10.1200/jco.2012.45.9735
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Recreational Physical Activity and Leisure Time Spent Sitting With Colorectal Cancer Survival

Abstract: More recreational physical activity before and after colorectal cancer diagnosis was associated with lower mortality, whereas longer leisure time spent sitting was associated with higher risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
186
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(201 citation statements)
references
References 33 publications
7
186
2
4
Order By: Relevance
“…Data from the oncology literature would suggest that physical exercise helps to overcome the fatigue during adjuvant therapy for breast cancer 58 and leads to lower mortality following colorectal cancer. 59 It goes without saying that adequate pain relief and minimal sedation facilitate mobilization, and therefore, integration of various elements is a necessity for better outcomes.…”
Section: Mobilizationmentioning
confidence: 99%
“…Data from the oncology literature would suggest that physical exercise helps to overcome the fatigue during adjuvant therapy for breast cancer 58 and leads to lower mortality following colorectal cancer. 59 It goes without saying that adequate pain relief and minimal sedation facilitate mobilization, and therefore, integration of various elements is a necessity for better outcomes.…”
Section: Mobilizationmentioning
confidence: 99%
“…A diet rich in fruits, vegetables, poultry, fish, whole grain, and poor in red meat and concentrated sweets was associated with better outcomes with regard to cancer recurrence or death. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Another important aspect of survivorship care is health promotion. Evidence suggests that noncancer comorbidities have a negative impact on overall quality of life and long-term survival when compared with the cancer diagnosis itself.…”
Section: Survivorshipmentioning
confidence: 99%
“…The meta-analysis also found that higher post-diagnosis physical activity level was associated with a significantly increased overall survival (HR overall survival = 0.62, 95% CI 0.54 to 0.71; fixed-effects model; p < 0.001). Five [31][32][33][34][35] out of the six individual studies assessing the relationship between physical activity level and overall survival found a statistically significant increase in overall survival among patients with higher post-diagnosis physical activity levels. Pooled relative risks from another meta-analysis 23 among CRC survivors showed inverse associations between post-diagnosis leisure-time physical activity and mortality based on six prospective cohorts.…”
Section: Physical Activity and Survivalmentioning
confidence: 99%
“…Three separate meta-analyses 23,28,29 including the same six observational studies [30][31][32][33][34][35] were published in 2013-14. Owing to different cut-off values for level of physical activity and different statistical analyses used, there is slight variation in the results; what is evident, however, is that all three studies show that a higher level of physical activity is associated with an increase in cancer-specific and overall survival.…”
Section: Physical Activity and Survivalmentioning
confidence: 99%
See 1 more Smart Citation